Amidine Derivatives of Avibactam: Synthesis and In Vitro β‐Lactamase Inhibition Activity. Issue 5 (3rd February 2021) - Gao, Yuanyu; Liu, Yuanbai; Iqbal, Zafar; Sun, Jian; Ji, Jinbo; Zhai, Lijuan; Tang, Dong; Ji, Jingwen; He, Lili; Mu, Yangxiu; Yang, Haikang; Yang, Zhixiang
Abstract: Avibactam is a non‐β‐lactam based second generation β‐lactamase inhibitor containing diazabicyclooctane (DBO) ring as the β‐lactam mimic. We substituted C2 position of DBO scaffold by a number of amidine derivatives to form water soluble final compounds A1 ‐A14 . The synthesized compounds were evaluated for their antibacterial and synergistic activity in combination with an antibiotic in vitro . The compounds, were tested against ten bacterial strains alone and in combination with existing antibiotic, meropenem. All compounds didn't show antibacterial activity when alone (MIC, >128 μM), however exhibited moderate to good synergistic activity in the presence of meropenem by lowering its MIC values. Compound A7 proved the most potent among other counterparts against all bacterial species with MIC from <0.29 μM to 2.34 μM, and showed comparable or improved activity to avibactam against eight bacterial strains. Compound A7 may prove a lead for next level in vivo and clinical studies. Abstract : Multistep synthesis of amidine substituted avibactam derivatives has been achieved starting from commercially available precursor. All compounds exhibited no antibacterial activity alone however showed variable MIC values in combination with meropenem against ten bacterial species expressing different β‐lactamases. Compound A7 proved the best one showing comparable or improved activity to Avibactam in case of eight out of ten bacterial strains.